Predictor of Postpartum Depression: Literature Review - Lestari, Indah; Saudah, Noer; Rofi’ah, Ika Ainur; Nugroho, Heru Santoso Wahito (Poltekkes Kemenkes Palu, 2023)
The incidence of postpartum depression is quite high. The largest percentage occurs when they have their first child, and have a family history of mood disorders. The incidence of postpartum depression is 50 - 60% in mothers when they have their first child, and around 20% in mothers who give birth to subsequent children. This study aims at reviewing and synthesizing the determinants factor of depression among adolescent in rural area. This study design was a systematic review using the PICO framework. This data was carried out from various journal databases 2012-2022, including Scopus, ScienceDirect, PubMed. 16 articles meet the inclusion criteria and meet the qualifications for review. A systematic procedure is used to collect articles, as well as a critical appraisal and data synthesis with qualitative synthesis. The analysis of the literature review found that aspects of findings related to predictors of postpartum depression are as follows: socio-demographic factors (age, socio-economic status, education, risk age group), maternal factors (pregnancy spacing, parity, pregnancy condition, birth experience, postpartum complications), biological factors (hypothalamus function, prolactin, CRH, inflammatory process), psychosocial factors (negative mood, anxiety, unpreparedness, history of depression), cultural factors (children care stress, wisdom), support system (support husband, family support, decision-making patterns). Healthcare professionals should be aware of this phenomenon and strategies such as primary, secondary, and tertiary prevention interventions may be applied. Women should be screened for potential risk factors and depressive symptoms during pregnancy and postpartum periods so that appropriate interventions if needed, can be initiated in a timely fashion.